Analysis On Seepage Through Senggarang Coastal Embankment In Johor, Malaysia. - Rosli, Arif Fikri; Mohd Arish, Nur Aini (Progress in Engineering Application and Technology, 2023)
Seepage is one of the most common problems experienced with embankments. Due to soil permeability and pore pressure inside the porous medium, seepage is a critical phenomenon that occurs at Senggarang Coastal Embankment(SCE). In this study, seepage occurred in the inland region, causing flooding and harming the crops. The goal is to monitor and record the seepage rate along the chosen point of the embankment. This point was chosen based on the severity of the seepage and the location’s accessibility. A seepage profile and its relationship to the tidal effect on the embankment will be derived from the acquired result. A direct shear test was conducted in the lab to figure out the shear strength of the soil for the Senggarang coastal embankment. During the arrangement of the field investigation, 2 distinct points with the most significant seepage were identified. The seepage analysis was conducted on November 11 and 12, 2022, during the highest chart tide of the month. This also applies to collecting the soil sample for the direct shear test to determine the slope’s cohesion value. The analysis reveals that the seepage rate appears proportional to the rise in tide height and the volume of water discharged by seepage at points 1 and 2. The direct shear test evaluates the amount of cohesion which leads to the findings that the embankment has a very low cohesion value which causes the seepage issue to happen. At the end of the study, the seepage condition for SCE is alarming and requires immediate attention to prevent the embankment from collapsing. Changing the soil profile to a better cohesive type of soil will eventually decrease the amount of seepage.